2011
DOI: 10.1007/s11096-011-9483-4
|View full text |Cite|
|
Sign up to set email alerts
|

Breast cancer health promotion in Qatar: a survey of community pharmacists’ interests and needs

Abstract: Despite their low involvement in breast cancer health promotion, the majority of pharmacists were interested in educating patients about breast cancer. However, low breast cancer knowledge and other barriers can prevent actualizing this role. Further work should focus on providing these pharmacists with breast cancer continuous education and overcoming all stated barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 26 publications
(20 reference statements)
2
41
0
Order By: Relevance
“…In a Qatar study, 78% of the pharmacists queried revealed that they never distributed breast cancer educational materials. Despite their current low involvement, more than 60% of the pharmacists expressed a high interest in becoming involved in breast cancer health promotion activities (El Hajj and Hamid, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In a Qatar study, 78% of the pharmacists queried revealed that they never distributed breast cancer educational materials. Despite their current low involvement, more than 60% of the pharmacists expressed a high interest in becoming involved in breast cancer health promotion activities (El Hajj and Hamid, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Community pharmacists could play a vital role to educate the public about breast cancer and the importance of early detection (El Hajj and Hamid, 2011). As reported by Anderson (2000) and Krass et al (2003) …”
Section: Introductionmentioning
confidence: 97%
“…However, most of the patients in Malaysia present with advanced stage of the disease on their initial visit to the public hospitals (Hisham and Yip, 2004; Nur et al, 2007). Hence, there is a need to facilitate the early breast cancer detection (Hadi et al, 2010).Community pharmacists could play a vital role to educate the public about breast cancer and the importance of early detection (El Hajj and Hamid, 2011). As reported by Anderson (2000) and Krass et al (2003) …”
mentioning
confidence: 99%
“…Studies indicate that doctors often do not offer BCS services to women. Other health care providers (HCP) might not have adequate knowledge of BCS and risk factors related to breast cancer in the Middle East, thus limiting their ability to encourage patients to engage in BCS activities (Bener et al, 2001;Haji-Mahmoodi, 2002;Madanat and Merrill, 2002;Dow Meneses and Yarbro, 2007;Alkhasawneh et al, 2009;Jaradeen, 2010;El Hajj and Hamid, 2011). Previous studies in the region indicate low participation rates in breast cancer screening activities among women (Bener et al, 2001;Bener et al, 2002;Azaiza and Cohen, 2008;Bener et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate and varied sources of information about breast health and BCS from health care providers (especially physicians), mass media, and social networks can positively influence women's knowledge and practice of BCS (Al-Qattan, et al, 2007;Dandash and Al-Mohaimeed, 2007;Montazeri, et al, 2008;Hoffman et al, 2010). Facilitators of BCS behavior include having support from male relatives, receiving information about breast cancer or BCS from health care professionals (HCP) other than doctors, and having a doctor's recommendation (Haji-Mahmoodi, 2002;Madanat and Merrill, 2002;Cohen and Azaiza, 2005;Azaiza and Cohen, 2006;Shirazi et al, 2006;Dandash and Al-Mohaimeed, 2007;Dow Meneses and Yarbro, 2007;El Saghir et al, 2007;Alkhasawneh et al, 2009;Gürsoy et al, 2009;Jaradeen, 2010;El Hajj and Hamid, 2011).…”
Section: Introductionmentioning
confidence: 99%